Information Management of Demand-responsive Mobility Service Based on Autonomous Vehicles. (2017) - Szigeti, Szilárd; Csiszár, Csaba; Földes, Dávid
Abstract: The autonomous road vehicle (AV) technology implies significant alteration of urban mobility services. The identified transit modes based on AVs are the individual cars, the demand-responsive public transportation with small or medium sized pods and the high capacity public transportation on arterial routes. The introduction of the telematics-based, shared, demand responsive mobility service requires new information management methods. Accordingly, the aim of our research was to model the structure and the operation of this rather complex information system considering both the operators and the users. Since the passenger functions are the keys of the advanced information service the conceptual plan of the mobile application with personalized functions has been also elaborated. The research questions were: how the architecture and the functions of the information system are to be modelled, what the novel information management functions of passengers and operators are, what data structure is needed and how it is related to the functions as well as what kind of functions are to be realized in the mobile application. The results are applicable as foundations for innovation and development projects aiming realization of either the back-end or the front-end components and for planning information management processes.